Investors’ Perception for Transforming Traditional Stock Market into Islamic Stock Market: An Empirical Study on Dhaka Stock Exchange - Mondal, Md. Saheb Ali; Akter, Nazma; Kamal, Mohammad Afsar (ABC Journal of Advanced Research, 2013)
Muslim investors should concern not only about maximizing profits but also be aware about the justification of Islamic guidelines and invest to whose stocks which are shariah compliant. The severity of the current market fall as well as financial crisis has shaken the foundations of the capitalist financial and capital market system and has led to search for ideas and solutions. So it is imperative to explore all possible approaches that enhance the process of mobilizing Islamic financial resources and expanding shariah compatible investment like investment in Islamic stock market. This paper is few attempts that identify some failures of conventional stock market as well as favorable position of Islamic stock market and investors’ perception regarding the topic. Study covers 201 respondents to collect data and analyze it by using five point Likert scale. This study found that investors feel to get separate Islamic stock market with Islamic shariah and principles but not to transfer traditional stock market into Islamic stock market. The study revealed that they desire to get stable and minimum risk market for Islamic stock with halal income whereas they want to make more profit anyhow from the existing market preferably.